Desain Proyek Penguatan Profil Pelajar Pancasila (P5) dalam Kurikulum Merdeka di SMK Negeri 1 Sitolu Ori - Zendrato, Muli Adil; Bawamenewi, Adrianus; Lase, Berkat Persada; Harefa, Hendrikus Otniel Nasozaro (LPPM Institut Pendidikan Nusantara Global, 2024)
The Pancasila Student Profile Strengthening Project (P5) aims to achieve the Pancasila student profile through project-based learning with a new paradigm. This study aims to determine the design of the P5 project in the Merdeka Curriculum at SMK Negeri 1 Sitolu Ori, as well as the obstacles faced in the design process. This study uses a descriptive approach with a qualitative method, with researchers as the main instrument. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the design of the P5 project at SMK Negeri 1 Sitolu Ori began with the formation of a P5 facilitator team responsible for facilitating discussions and learning processes, both indoors and outdoors, as well as designing dimensions, themes, and time allocations to ensure a smooth learning process. Obstacles faced in the design of P5 include limited time and resources, where teachers need more time and resources compared to traditional learning. Teachers also need to provide books, tools, and materials needed by students. In addition, the lazy attitude of some students and the limited media owned by teachers are also obstacles in the teaching and learning process. Efforts to overcome these obstacles include providing students with a better understanding of the goals and components of P5, designing P5 activities according to students' interests and talents, and understanding the goals and principles of the Pancasila student profile strengthening project at SMK Negeri 1 Sitolu Ori.